Financial Burden and Mental Health Among LGBTQIA+ Adolescent and Young Adult Cancer Survivors During the COVID-19 Pandemic - Waters, Austin R.; Bybee, Sara; Warner, Echo L.; Kaddas, Heydon K.; Kent, Erin E.; Kirchhoff, Anne C. (Frontiers in Oncology, 2022)
Background: In the United States, the cost of cancer treatment can lead to severe financial burden for cancer survivors. The economic impacts of the COVID-19 pandemic compound cancer survivors’ financial challenges. Financial burden may be particularly challenging for lesbian, gay, bisexual, transgender, queer, intersex, asexual and other sexual and gender minority (LGBTQIA+) survivors. LGBTQIA+ survivors who are adolescent and young adults (AYA) may face elevated financial burden due to multiple, intersecting identities. Methods: An explanatory sequential mixed methods design was applied, beginning with a survey of AYA cancer survivors in the Mountain West region of the United States. Survey measures included demographics, COVID-19 impacts, the COmprehensive Score for financial Toxicity (COST), Perceived Stress Scale-4 (PSS-4), and PROMIS anxiety and depression scales. Two-way t-tests were used to analyze differences in outcomes between LGBTQIA+ and non-LGBTQIA+ AYAs. All LGBTQIA+ survey participants were invited to complete an interview, and those who agreed participated in descriptive interviews about financial burden due to cancer, COVID-19, and LGBTQIA+ identity. Interviews were audio recorded, transcribed, and analyzed using Dedoose. Results: Survey participants (N=325) were LGBTQIA+ (n=29, 8.9%), primarily female (n= 197, 60.6%), non-Hispanic White (n= 267, 82.2%), and received treatment during COVID-19 (n= 174, 54.0%). LGBTQIA+ interview participants (n=9, 100%) identified as a sexual minority and (n=2, 22.2%) identified as a gender minority. Most were non-Hispanic White (n=6, 66.7%) and had received treatment during COVID-19 n=7, 77.8%). Statistical analyses revealed that LGBTQIA+ AYAs reported significantly worse COST scores than non-LGBTQIA+ AYAs (p=0.002). LGBTQIA+ AYAs also reported significantly higher PSS-4 (p=0.001), PROMIS anxiety (p=0.002) and depression scores (p<0.001) than non-LGBTQIA+ AYAs, reflecting worse mental health outcomes. High costs of cancer treatment and employment disruptions due to COVID-19 contributed to substantial financial stress, which exacerbated existing mental health challenges and introduced new ones. Conclusions: LGBTQIA+ AYA survivors reported substantial financial burden and psychological distress exacerbated by cancer, the COVID-19 pandemic, and LGBTQIA+ stigma. Given their multiple intersecting identities and potential for marginalization, LGBTQIA+ AYA survivors deserve prioritization in research to reduce financial burden and poor mental health.